Nifekalant versus Amiodarone for Out-Of-Hospital Cardiac Arrest with Refractory Shockable Rhythms; a Post Hoc Analysis - Funakoshi, Hiraku; Aso, Shotaro; Homma, Yosuke; Onodera, Ryuta; Tahara, Yoshio (Archives of Academic Emergency Medicine, 2022)
Introduction: It is still unclear that which anti-arrhythmics are adequate for treating refractory dysrhythmia. This study aimed to compare amiodarone and nifekalant in management of out-of-hospital cardiac arrest cases with refractory shockable rhythm. Methods: This was a post hoc analysis of cases registered in a nationwide, multicentre, prospective registry that includes 288 critical care medical centres in Japan. From June 2014 to December 2017, we included all out-of-hospital cardiac arrest patients aged ≥18 years who presented with refractory arrhythmia (sustained ventricular fibrillation or ventricular tachycardia following delivery of at least two defibrillator shocks) and treated with nifekalant or amiodarone after arrival to hospital. Overlap weight was performed to address potential confounding factors. Results: 1,317 out-of-hospital cardiac arrest patients with refractory arrhythmia were enrolled and categorized into amiodarone (n = 1,275) and nifekalant (n = 42) groups. After overlap weight was performed, there were no significant intergroup differences in increased the rate of admission after return of spontaneous circulation [–5.9% (95%CI: –7.1 to 22.4); p = 0.57], 30-day favourable neurological outcome [0.1% (95%CI: –14 to 13.9); p = 0.99], and 30-day survival [–3.9% (95% CI: –19.8 to 12.0); p = 0.63]. Conclusion: This nationwide study showed that nifekalant was not associated with improved outcomes regarding admission after return of spontaneous circulation, 30-day survival, and 30-day favourable neurological outcome compared with amiodarone.